Faithful expression of imprinted genes in donor cells of SCNT cloned pigs. Issue 16 (25th June 2015) - Wang, Dongxu; Yuan, Lin; Sui, Tingting; Song, Yuning; Lv, Qingyan; Wang, Anfeng; Li, Zhanjun; Lai, Liangxue
Abstract : To understand if the genomic imprinting status of the donor cells is altered during the process of SCNT (somatic cell nuclear transfer), cloned pigs were produced by SCNT using PEF (porcine embryonic fibroblast) and P‐PEF (parthenogenetic‐PEF) cells as donors. Then, the gene expression and methylation patterns of H19, IGF2, NNAT and MEST were compared between PEF vs . C‐PEF (cloned‐PEF), P‐PEF vs . CP‐PEF (cloned‐P‐PEF), respectively. Taken together, the results revealed that there was no significant difference in the expression of imprinted genes and conserved genomic imprints between the donor and cloned cells. Abstract : Cloned pigs were produced by SCNT using PEF and P‐PEF cells as donors. The gene expression of H19, IGF2, NNAT and MEST were analyzed by qRT‐PCR. The methylation patterns of H19, NNAT and MEST were analyzed by BSP and COBRA. Faithful expression of imprinted genes between the donor and cloned cells.